Fecal bacteria and metabolite responses to dietary lysozyme in a sow model from late gestation until lactation - Xu, Shengyu (Sci Rep, 2020)
Lysozyme (LZM) is a natural anti-bacterial protein that is found in the saliva, tears and milk of all mammals including humans. Its anti-bacterial properties result from the ability to cleave bacterial cell walls, causing bacterial death. The current study was conducted to investigate the effects of dietary LZM on fecal microbial composition and variation in metabolites in sow. The addition of LZM decreased the fecal short-chain fatty acids (SCFAs). Zonulin and endotoxin in the serum, and feces, were decreased with lysozyme supplementation. Furthermore, fecal concentrations of lipocalin-2 and the pro-inflammatory cytokine TNF-α were also decreased while the anti-inflammatory cytokine IL-10 was increased by lysozyme supplementation. 16S rRNA gene sequencing of the V3-V4 region suggested that fecal microbial levels changed at different taxonomic levels with the addition of LZM. Representative changes included the reduction of diversity between sows, decreased Bacteroidetes, Actinobacteria, Tenericutes and Spirochaetes during lactation as well as an increase in Lactobacillus. These findings suggest that dietary lysozyme supplementation from late gestation to lactation promote microbial changes, which would potentially be the mechanisms by which maternal metabolites and inflammatory status was altered after LZM supplementation.